2017
DOI: 10.1038/onc.2017.354
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A-mediated phosphorylation of LKB1 compromises LKB1/AMPK signaling axis to facilitate NSCLC growth and migration

Abstract: Deletion or loss-of-function mutation of LKB1, frequently occurring in non-small cell lung cancers (NSCLCs), is a predominant caution of NSCLC initiation and progression. However, the upstream signaling pathways governing LKB1 activation are largely unknown. Here, we report that LKB1 undergoes Aurora kinase A (AURKA)-mediated phosphorylation, which largely compromises the LKB1/AMPK signaling axis, in turn leading to the elevation of NSCLC cell proliferation, invasion and migration. Mechanically, AURKA-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Many researchers have found that four key genes were involved in cell cycle, participating in tumorigenesis and tumor proliferation. AURKA has been studied in a wide range of human malignancies and is associated with poor prognosis in several malignancies, including cervical squamous cell carcinoma, hepatocellular carcinoma, and nonsmall cell lung carcinoma (Ma et al, ; Wang et al, ; Zheng et al, ). Besides, Yang et al, () reported that AURKA as a transactivating co‐factor in the induction of the c‐Myc oncoprotein in breast cancer stem cells (BCSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that four key genes were involved in cell cycle, participating in tumorigenesis and tumor proliferation. AURKA has been studied in a wide range of human malignancies and is associated with poor prognosis in several malignancies, including cervical squamous cell carcinoma, hepatocellular carcinoma, and nonsmall cell lung carcinoma (Ma et al, ; Wang et al, ; Zheng et al, ). Besides, Yang et al, () reported that AURKA as a transactivating co‐factor in the induction of the c‐Myc oncoprotein in breast cancer stem cells (BCSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a contributor to NSCLC progression [1012], and C5a can cause tumor cell proliferation [8, 9, 28, 29]. However, how C5a affects tumor cell proliferation in NSCLC still remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that C5a is associated with tumor growth [4, 5], and C5a in tumor microenvironment not only acts as a leukocyte chemoattractant [4, 5], but also promotes tumor cell proliferation [68]. Non-small cell lung cancer (NSCLC) is the most common type of lung cancer [9]. Although many researchers have uncovered that inflammatory cytokines or mediators, e.g., C5a are involved in NSCLC carcinogenesis and proliferation [1012], the mechanism of C5a governing NSCLC cell proliferation remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although AMPK regulates mTOR as part of the mTOR complex 1 (mTORC1) and AKT S473 is an mTORC2 target site, it has been recently shown that AMPK activation can also reduce mTORC2 activity and AKT S473 phosphorylation in NSCLC cells (55). Interestingly, recent studies found that inhibition of AURKA can overcome mTOR inhibitor resistance in gastrointestinal cancer cells and that AURKA can repress STK11(LKB1)/AMPK signaling in NSCLC cells (56,57). These data agree with our findings that AURKA inhibition is a major component of midostaurin's MoA, maybe even more so in STK11-wild-type cells.…”
Section: Molecular and Cellular Proteomics 1712 2443mentioning
confidence: 99%